Caracterização das emissões gasosas provenientes da queima de biomassa de bagaço de cana de açúcar - Tempesta, Henrique Novaes (2022)
Faced with increasingly frequent natural disasters, and a future that is not encouraging in relation to the environmental problems that the planet will suffer in the near future, people, governments and companies are beginning to rethink their roles in society. One of the ways to reduce the effect of global warming is through the use of biomass as fuel in combustion processes, replacing petroleum derivatives. In Brazil, the most prominent biomass for this use is sugarcane bagasse, derived from the sugar-alcohol industry. However, several aspects of a fuel must be evaluated to determine whether its use is environmentally viable, such as determining pollutant emissions from the combustion process. This work aimed to determine the concentration of CO, CO2, NO2, NOx, SO2 formed in this process and to evaluate the control of these pollutants. Sampling took place in a burner equipped with a scrubber Venturi, an equipment used industrially to reduce the amount of pollutants emitted into the atmosphere. A gas sampler was positioned in the chimney of the burner, making it possible to carry out the experiments. The concentration results were between 19 and 20% for CO2, 44.40 and 256.98 ppm for CO, 0.97 and 3.44 for NO2, 3.44 to 32.48 ppm for NOx and 0 to 3.14 ppm for SO2. This study proves to be relevant in order to enrich the literature on the subject, in addition to serving as inspiration for new studies and encouraging the use of this biomass as an energy source. Finally, the results were close to another research carried out with bagasse, and smaller than most similar projects carried out with other raw materials, in addition, emissions were within the limits established by current legislation.